Оцінка клінічної ефективності комплексного лікування трофічних виразок нижніх кінцівок у хворих на цукровий діабет - Сергієнко, О. О.; Маркевич, Ю. О.; Сергієнко, В. О. (Clinical Endocrinology and Endocrine Surgery, 2011)
The aim of this study was to evaluate the clinical efficacy and safety of Delaskin, Fusicutan and Vulnostumulin for local use in patients with diabetes mellitus (DM) and trophic ulcers of lower extremities I-II grades by Wagner in comparison with conventional treatment; to identify any possible topical and general side effects. 42 patients with DM and trophic ulcers of lower extremities were observed, among them 20 patients were treated with Delaskin, Fusicutan and Vulnostumulin in complex treatment (main group), 22 patients as control group received standard treatment. It was established that complex topical treatment with Delaskin, Fusicutan and Vulnostumulin can be recommended as for both inpatient and outpatient treatment of trophic ulcers as well as preparation for dermatoplasty. Delaskin, Fusicutan and Vulnostumulin are effective medications in complex sequential local treatment and prevention of infectious complications in patients with DM and trophic ulcers of lower extremities and they are appropriate for the widespread use of by clinicians.